System-School Alignment in Support of Teacher Leadership: An Australian Case Study - Conway, Joan M.; Andrews, Dorothy; Trimmer, Karen (International Journal of Education Policy and Leadership, 2025)
This article reports on a case study from Australia contributing to a global research project that explores concepts and definitions of teacher leadership in 12 countries using a three-phase data collection approach: an initial literature review; a survey developed from themes in the literature and conducted in each of the countries; and semi-structured interviews designed to explore in depth the understanding of teacher leadership as perceived by the participants in each country, which is the focus of this article. The findings show a lack of coherence regarding expectations of teachers as leaders and teacher leadership, and emphasizes the need for a system-school alignment in support of teacher leadership wherein the principal and the teachers are respectfully acknowledged and supported as the custodians of their context.